Petroleum pitch derived carbon as both cathode and anode materials for advanced potassium-ion hybrid capacitors. (30th August 2022) - Wu, Chenghao; Xu, Qian; Ning, Hui; Zhao, Yan; Guo, Shiwei; Sun, Xitong; Wang, Yujuan; Hu, Han; Wu, Mingbo
Abstract: Potassium-ion hybrid capacitors (PIHCs) are considered as ideal devices for large-scale electrochemical energy storage because of their low reduction potential, environmental-friendly and abundant potassium resources in the earth. However, the simple and eco-friendly preparation of well-matched cathode and anode materials is still with great challenges. With the same petroleum pitch (with asphaltenes removed by n-heptane) as carbon source, herein we reported low-cost and non-corrosive processes to construct two carbon materials, namely soft carbon nanosheets (SCNs) and active carbon nanosheets (ACNs), as anode and cathode materials, respectively, to assemble high performance PIHCs. The SCNs with expanded graphitic interlayer spacing of 0.396 nm and abundant surface defects present super rate capability and high pseudocapacitive proportion. In addition, the ACNs with hierarchical pores structure, which accelerates the adsorption and transport of electrolyte ions, exhibit outstanding capacitive performance. By optimizing the voltage window and mass ratio of cathode and anode, the SCNs//ACNs PIHCs deliver a high energy density of 124.0 Wh kg −1 at a power density output of 198.9 W kg −1 and an ultralong lifespan over 9000 cycles. This work opens a new avenue to increase the value-added utilization of petroleum pitch for innovative potassium-based energy storage technology. Graphical abstract: Image 1